Prosedur Badan Penyelengara Jaminan Sosial Dalam Klaim Jaminan Kecelakaan Kerja (International Forum of Researchers and Lecturers, 2023)
Work accidents are a phenomenon that often occurs in various industrial sectors. In the process of nation building, the role of the workforce is increasing, along with the various difficulties and risks they face. As a result, to increase national productivity, workers must be provided with protection, care and increased welfare. To ensure that all the steps required to obtain work accident insurance have been carried out correctly and clearly, BPJS procedures cover various aspects, such as registering participants, handling work accident cases, and paying compensation to victims. This journal is made using the library research method, which refers to the process of searching, collecting and analyzing literature or written sources such as books, reports and journals that are relevant to a particular research or study topic. One of them is for the workforce in realizing prosperity. Due to the important role of labor in achieving development goals, they have rights and obligations protected by law. Workers who experience work accidents can receive legal protection such as health services according to medical needs and monetary compensation. The rights and obligations of workers, employers and BPJS Employment are not affected if reporting work accidents is delayed to BPJS Employment and UPTD Employment Inspection.